Documental Mindo una ventana al ecoturismo - Montalvo Gómez de la Torre, Cristian Eduardo (2015)
In a changing and dynamic modern world, there is an urgent need to adapt to different scenarios, mainly learning about ourselves and our environment, to take full advantage of the situations. This is the case of Ecotourism, a new term emerges from the need to rethink the ways in which tourism is operated nowadays, where its value lays on the exploitation of the location and its resources are centered on the materialistic development of the area. Large touristic companies are taking the bulk of the profits and in most cases the hosts are being trampled socially, their culture unappreciated, their history ignored and the people abused. We do not have a sense of the real value for conservation as a means of developing a notion of sustainable, reliable and decent growth. Here is where ecotourism gives us the opportunity to create a more feasible and permanent environment for conservation in order to obtain a viable alternative from the output of classic tourism. Introducing new ways and methods for a more sustainable culture of tourism will give us over time the opportunity to set aside the actual norm of waste and abuse to the natural environment. We need to create ways for development based on the respect for all living things by raising awareness through education focusing on the need of maintaining a healthy nation. The development of techniques and strategies to aid the public on the necessary information and intellectual resources will be a key factor that will take us from a wasteful society to a more eco friendly existence. Starting in primary levels will allow us to set a value for the proper management of nature and its resources, where all the people involved will have a direct investment and active participation including various authorities as to benefit us all. From the parish to the entire world will enjoy the benefits of conservation and proper management of resources as it is crucial and increasingly required.